Evaluation of the Health Center Management Information System (SIMPUS) Implementation trough PIECES and HOT-Fit Methods at the Puskesmas (Community Health Center) Limboto - Arshinta Zuhriany Koem; Sylva Flora Ninta Tarigan; Tri Septian Maksum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The Health Center Management Information System (SIMPUS) is a service for managing patient data starting from the registration stage, examination to patient treatment. The application of SIMPUS needs to be evaluated in order to improve the quality of health services which can be done using the PIECES and HOT-Fit approaches/methods. The PIECES method consists of six assessment indicators including performance, information, economy, control, efficiency and service. The HOT-Fit method consists of four assessment indicators including human, organization, technology and benefits. The aim of the research is to evaluate the implementation of SIMPUS using the PIECES method and the HOT-Fit method at the Limboto Community Health Center. This type of research is descriptive with quantitative methods. The population is all health workers who use the SIMPUS application at the Limboto Community Health Center, totaling 62 health workers. The number of samples is the same as the population, namely 62 people, which was obtained using exhaustive sampling techniques. The data was analyzed descriptively and then presented in the form of a frequency distribution table. The results of the research show that the evaluation of the application of SIMPUS using the PIECES method was obtained by the majority of respondents (53.2%) stating that it was not good, while the majority of respondents (64.5%) also stated that it was not good for the HOT-Fit method. It is recommended that the Limboto Community Health Center improve the quality of SIMPUS by focusing more on routine evaluations, improving HR skills, strengthening integration between applications, as well as improving infrastructure and system security.